Peran Pemuda dalam Penyadaran Konflik di Kota Ambon (Studi Kasus: Komunitas Non-Violent Study Circle) - Perdana, Prasojo Yekti (Multiverse: Open Multidisciplinary Journal, 2023)
This research aims to analyze the role of the NVSC community in raising conflict awareness in Ambon City. The study employs a qualitative method with a case study research design. Key informants identified by the researcher include the Founder of the NVSC Community (JN), Field Coordinator (YK), and Deputy Field Coordinator (DK). Data collection utilizes observation techniques, interviews, and document reviews. The analysis involves examining information from various sources, such as in-depth interviews, documentation, and observation. The results indicate that, in executing peacekeeping missions, the NVSC community relies solely on local connections without considering critical aspects, such as conflict sources, involved parties, behaviors, and attitudes in the target regions. The researcher recommends that agents of peace within NVSC should possess conflict mapping skills to comprehend the intricacies of the areas they aim to empower.